Dairy industry effluent treatment and valorisation in a two chambered microbial fuel cell - Faria, A. (2014)
The capacity of some microorganisms to transfer electrons directly to an anode might be an opportunity to wastewater valorisation. Therefore, the main goal of the present work was to evaluate and optimize the performance of a microbial fuel cell (MFC) for continuous dairy industry wastewater treatment. A two compartment MFC with a liquid volume of 400 cm3 was used and the voltage was recorded along time. The produced voltage was around 500 mV and a power density of ~50 mW/m2 was obtained. Regarding the carbon removal, the maximum was achieved after 20 days of continuous operation corresponding to a removal of 63%. In conclusion the tested MFC was able to treat a dairy effluent and at same time to produce bioelectricity, proving to be a promising and sustainable technology for wastewater treatment.